Intraoperative navigation in oral and maxillofacial surgery - Haßfeld, Stefan; Mühling, Joachim; Zöller, Joachim E. (International journal of oral and maxillofacial surgery, 1995)
Surgical procedures in the oral and maxillofacial region may be difficult in areas of complex anatomy. Up to now, surgical planning has been based almost exclusively on the surgeon's experience and on the interpretation of 2-dimensional (2D) radiologic information. Our experiences with a commercially, available 3D navigation system (Viewing Wand, ISG, Mississauga, Ontario, Canada) is reported upon. The system consists of a mechanical operating arm with 6 joints and 6 degrees of freedom working as a 3D digitizer and is interfaced to a computer graphics workstation. After registration of the position of the patient's head in relation to the tip of the instrument on the navigation arm, the surgeon can observe the 3D position and direction of the instrument in use on the monitor, i.e. on the computed tomography and/or magnetic resonance tomography images of the patient taken before. In 40 interventions performed so far, the accuracy was 2 mm and better. 3 cases are presented in this paper. The system facilitates surgery especially in anatomically complicated situations without the risk of damaging neighbouring structures. Planning of surgical interventions is much easier. By using computer assisted simulation and navigation systems, we expect an improvement in quality and a reduction in surgical risks. Thus, “looking ahead” surgery has become possible. More extensive and more radical interventions are likely to be performed in the near future. Responsibility for the surgical intervention, however, remains exclusively with the surgeon. - Operative Eingriffe im Mund-Kiefer-Gesichtsbereich können aufgrund der komplexen anatomischen Verhältnisse Schwierigkeiten bereiten. Insbesondere Operationsplanungen basieren bisher nahezu ausschließlich auf Erfahrungswerten des operierenden Arztes und der Auswertung 2-dimensionaler (2D), statischer Informationsquellen. Es wird über unsere Erfahrungen mit einem kommerziell verfügbaren 3D Navigationssystem (Viewing Wand, ISG, Mississauga, Ontario, Canada) berichtet. Das System besteht aus einem Gelenkarm, der als 3D Raumkoordinatenmesser arbeitet und einer Graphik-Workstation. Nach der Registrierung der relativen Lage des fixierten, Patientenkopfes zum Navigationsarm ist es dem Chirurgen intraoperativ möglich, die aktuelle räumliche Position und Richtung der von ihm geführten Instrumente in Relation zu den computertomographischen und/oder magnetresonanztomographischen Daten des Patienten auf dem Monitor direkt zu verfolgen. Bei bisher 40 Eingriffen lag die Präzision des Systems im Bereich <2mm, 3 Fallbeispiele werden demonstriert. Die vorgestellte Technik ermöglicht Operationen auch bei anatomisch schwierigen Situationen ohne Gefährdung wichtiger Nachbarstrukturen. Die Operationsplanung wird entscheidend verbessert. Wir erwarten von computergestützten Simulations-und Navigationssystemen eine Qualitätsverbesserung und eine Verringerung der operativen Risiken. Ein «vorausschauendeså Operieren ist möglich geworden. Umfassendere und auch radikalere Eingriffe erscheinen durchführbar. Die Verantwortung für den Eingriff liegt jedoch weiterhin allein beim Chirurgen.